An Air‐Stable Densely Packed Phosphorene–Graphene Composite Toward Advanced Lithium Storage Properties. Issue 12 (27th April 2016) - Zhang, Yu; Wang, Huanwen; Luo, Zhongzhen; Tan, Hui Teng; Li, Bing; Sun, Shengnan; Li, Zhong; Zong, Yun; Xu, Zhichuan J.; Yang, Yanhui; Khor, Khiam Aik; Yan, Qingyu
Abstract : Phosphorene, monolayer or few‐layer black phosphorus (BP), has recently triggered strong scientific interest for lithium/sodium ion batteries (LIBs/SIBs) applications. However, there are still challenges regarding large‐scale fabrication, poor air stability. Herein, we report the high‐yield synthesis of phosphorene with good crystallinity and tunable size distributions via liquid‐phase exfoliation of bulk BP in formamide. Afterwards, a densely packed phosphorene–graphene composite (PG‐SPS, a packing density of 0.6 g cm −3 ) is prepared by a simple and easily up‐scalable spark plasma sintering (SPS) process. When working as anode materials of LIBs, PG‐SPS exhibit much improved first‐cycle Coloumbic efficiency (60.2%) compared to phosphorene (11.5%) and loosely stacked phosphorene–graphene composite (34.3%), high specific capacity (1306.7 mAh g −1 ) and volumetric capacity (256.4 mAh cm −3 ), good rate capabilities (e.g., 415.0 mAh g −1 at 10 A g −1 ) as well as outstanding long‐term cycling life (91.9% retention after 800 cycles at 10 A g −1 ). Importantly, excellent air stability of PG‐SPS over the 60 days observation in maintaining its high Li storage properties can be achieved. On the contrary, 95.2% of BP in PG sample was oxidized after only 10 days exposure to ambience, leading to severe degradation of electrochemical properties. Abstract : A densely packed phosphorene–graphene composite is prepared by a simple and easily upscalable spark plasma sintering process, which exhibits much improved 1 st ‐cycle Coulombic efficiency, high volumetric capacity, good rate capabilities as well as an outstanding cycling life, especially robust air stability in maintaining its high Li storage properties.